Clinical and immunophenotypic characteristics of patients with chromosome 22q11.2 deletion syndrome: a single institution’s experience - Nepesov, Serdar (Turk Pediatri Ars, 2019)
AIM: The aim of this study was to identify the clinical and immunologic features of patients with 22q11.2 deletion syndrome who were followed up in our clinic. Thus, it is aimed to identify the syndrome early, choose the right treatment options according to humoral and cellular immunologic analysis, and enlighten how to follow up these kinds of patients with immunodeficiencies. MATERIAL AND METHODS: We retrospectively collected data by reviewing the files of 11 patients with 22q11.2 deletion syndrome who were followed up in our clinic between January 2003 and January 2015. The diagnoses were based on the patients’ clinical, genetic, and immunologic features. Demographic features, family history, initial symptoms on admission, physical findings, and results of immunologic studies of the patients. Age of diagnosis, treatment options, and clinical follow-up were evaluated. RESULTS: The patients’ diagnosis age ranged from 1-11 months and the most common symptoms of admission were cardiac murmur and atypical facial appearance, which were detected during a routine physical examination. All patients had cardiac anomalies, and four patients had a history of cardiovascular surgery. Eight patients (72.7%) had a history of severe infection; recurrent lower respiratory tract infections were reported in six patients (54.5%), pulmonary tuberculosis in one patient (9.1%), and moniliasis resistant to treatment was detected in one patient. None of the patients required intravenous immunoglobulin replacement therapy, and antibiotic prophylaxis was administered to two patients with lymphopenia. CONCLUSION: 22q11.2 deletion syndrome is a multi-systemic disorder that should be evaluated by a multidisciplinary team. It should be kept in mind for patients with neonatal hypocalcemic tetany or recurrent infections or atypical facial appearance with cardiac anomalies. Early diagnosis should lead to immunologic analysis and enable the choice of treatment. Preventive measures against infection is recommended for the patients with incomplete immunodeficiency, and thymus transplantation is recommended for patients with complete immunodeficiency.